2018
DOI: 10.1186/s13018-018-0881-3
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of platelet-rich fibrin for rotator cuff tears: a meta-analysis

Abstract: BackgroundThe aim of this meta-analysis was to evaluate the efficacy and safety of platelet-rich fibrin (PRF) in improving clinical outcomes in rotator cuff tears.MethodsWe searched the following databases: Pubmed, Embase, and Cochrane library databases from inception to April 2018. Studies that compared platelet-rich fibrin versus placebo for rotator cuff tears were included in this meta-analysis. Risk ratio (RR) with 95% confidence interval (CI) was pooled for discontinuous outcome, and weighted mean differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Nevertheless, our review had several differences compared with previous systematic reviews and meta-analyses [15][16][17] . First, the previous reviews included studies that involved intraoperative administration and sonographyguided postoperative administration of PRP.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, our review had several differences compared with previous systematic reviews and meta-analyses [15][16][17] . First, the previous reviews included studies that involved intraoperative administration and sonographyguided postoperative administration of PRP.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies have reported that PRP can potentially aid wound repair 10 , 11 , 22 . Nevertheless, the effects of PRP on rotator cuff repair remain controversial 15 17 . Delve into the previous studies 15 17 , some of these 15 , 16 stated that PRP application is effective in reducing retear rate and improving clinical outcome while the other 17 showed no improvement in both.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the association of PRF, unlike other platelet concentrates, with progressive release of cytokines during fibrin matrix remodelling, application of growth factor mixtures through PRF maps is considered a potential approach for tendon-bone insertion regeneration such as rotator cuff repair (64). Accordingly, sutu-ring PRF side-to-side to close the tear in patients with rotator cuff tear was reported to be associated with improved range of motion and pain relief alongside the decrease in the re-tear rates (65,66).…”
Section: Rotator Cuff Tearmentioning
confidence: 99%
“…Platelet-rich fibrin (PRF) has been applied increasingly in regenerative dentistry and orthopedic surgery. PRF is derived from platelet-rich plasma and is characterized by its simple preparation protocol that does not employ anticoagulants or coagulation factors [1,2,3,4,5,6,7]. However, the reproducibility and predictability of PRF therapy remains controversial, especially in the context of bone regeneration [8].…”
Section: Introductionmentioning
confidence: 99%